Applications of Nanoparticles Preparations on Wound: A New Approach for Wound Repair and Regeneration - Gupta, Vijayta; Gupta, Anuradha; Kant, Vinay (Asian Journal of Science and Applied Technology, 2019)
Wound healing is an inherent physiological response that aids restore cellular and anatomic continuity of a tissue. It is an intricate process and for a long time has been the subject of intense research. Impaired wound healing has resulted into socio-economical loss and decreased the quality of life of patient. So, there is always need to develop some alternative wound healing agent which can accelerate the healing mechanisms. The recent development of technology has provided a novel therapeutic modality in nanoparticles for use in wounds. Nanoparticles (NPs) are small entities that comprises of a hydroxyapatite core, which can bind ions, proteins, and other organic molecules from the surrounding environment. Nanotechnology has provided a new therapeutic route for wound treatment in clinical practice. This article aims to review the wound healing activities of nanoparticles during the past years.